Understanding the Process and Challenges for Return-to-Work Post-Hematopoietic Cell Transplantation from a Musculoskeletal Perspective: A Narrative Review - Jaleel Mohammed; Anne Gonzales; Hadeel R. Bakhsh; Volkova Alisa Georgievna; Jayanti Rai; Bindu Kancharla; Shahrukh K. Hashmi (Occupational Therapy International)
The current paper seeks to inform healthcare professionals on how adapting various components of return to work (RTW) programs that are already in use by other musculoskeletal rehabilitation settings can help optimize return to work process for patients with or without musculoskeletal manifestations, posthematopoietic cell transplantation. Since there is no universally agreed RTW structure for hematopoietic cell transplant patients, a narrative approach has been taken utilizing evidence from the existing musculoskeletal return to work assessment publications to help draw parallel for the hematopoietic cell transplant patients. Databases were searched including PUBMED, CINHAL, AMED, SCOPUS, and Cochrane using keywords RTW, functional restoration program, hematopoietic cell transplant, bone marrow transplant, stem cell transplant, and musculoskeletal functional assessment. The authors have managed to outline and propose a structured RTW assessment and monitoring program which can aid in getting patients back to employment by utilizing the functional capacity and job evaluation to help hematopoietic cell transplantation patients reintegrate socially. Patients undergoing hematopoietic cell transplant require additional support and a robust assessment system to allow safe RTW. The proposed model of RTW assessment can prove to be beneficial in helping patients return to work safely. Clinical Significance. To acknowledge the individuality in functional limitation is important in determining not only the rehab needs but also the RTW capabilities. The proposed RTW plan not only promotes an individualized approach to patients but also provides a structure for return to work assessments for hematopoietic cell transplantation patients, thus, eliminating the need for guess work by healthcare professionals. In line with the International Classification of Functioning, Disability, and Health (ICF) recommendations, a RTW assessment combined with a job evaluation helps healthcare professionals and stakeholders to understand the unique challenges and strengths of a patient and thereby design an individualized therapy approach.